Golf steps to success - Schempp, Paul G.; Mattsson, Peter 1970-
Provides detailed, progressive instruction with accompanying full colour photographs for every shot, from putts, chip shots, and pitch shots to shots from the fairway, off the tee, bunker and rough and bad lies.